Apes produce tools for future use. Issue 3 (18th September 2014) - Bräuer, Juliane; Call, Josep
<x xml:space="preserve">Abstract</x> There is now growing evidence that some animal species are able to plan for the future. For example great apes save and exchange tools for future use. Here we raise the question whether chimpanzees, orangutans, and bonobos would produce tools for future use. Subjects only had access to a baited apparatus for a limited duration and therefore should use the time preceding this access to create the appropriate tools in order to get the rewards. The apes were tested in three conditions depending on the need for pre‐prepared tools. Either eight tools, one tool or no tools were needed to retrieve the reward. The apes prepared tools in advance for future use and they produced them mainly in conditions when they were really needed. The fact that apes were able to solve this new task indicates that their planning skills are flexible. However, for the condition in which eight tools were needed, apes produced less than two tools per trial in advance. However, they used their chance to produce additional tools in the tool use phase—thus often obtaining most of the reward from the apparatus. Increased pressure to prepare more tools in advance did not have an effect on their performance. Am. J. Primatol. 77:254–263, 2015. © 2014 Wiley Periodicals, Inc.